2022
DOI: 10.1007/s10585-022-10180-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemotherapy of skin metastases from malignant melanoma: a PRISMA-compliant systematic review

Abstract: The main treatment of MM metastases are systemic therapies, surgery, limb perfusion, and intralesional talimogene laherparepvec. Electrochemotherapy (ECT) is potentially useful also due to the high response rates recorded in cancers of any histology. No randomized studies comparing ECT with other local therapies have been published on this topic. We analyzed the available evidence on efficacy and toxicity of ECT in this setting. PubMed, Scopus, and Cochrane databases were screened for paper about ECT on MM ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
(276 reference statements)
0
5
0
Order By: Relevance
“…The mentioned factors may cause discomfort for patients. Nonetheless, ECT may offer an effective treatment for cancerous skin lesions: basal cell carcinoma, 100% complete response within 15–56 months ( Kis et al, 2019 ); melanoma metastases, 89% complete response within 24 months ( Ricotti et al, 2014 ) and 60% complete response within 6 months ( Matthiessen et al, 2011 ); and malignant melanoma, 53.5% ( Ferioli et al, 2022 ). Partial or negative tumor response may potentially be associated with inappropriate drug concentration, non-uniform PEF distribution, and other factors, including immune response to the treatment ( Sersa et al, 2008b ; Cadossi et al, 2014 ).…”
Section: Applications In Vivo and In Clinical Trialsmentioning
confidence: 99%
“…The mentioned factors may cause discomfort for patients. Nonetheless, ECT may offer an effective treatment for cancerous skin lesions: basal cell carcinoma, 100% complete response within 15–56 months ( Kis et al, 2019 ); melanoma metastases, 89% complete response within 24 months ( Ricotti et al, 2014 ) and 60% complete response within 6 months ( Matthiessen et al, 2011 ); and malignant melanoma, 53.5% ( Ferioli et al, 2022 ). Partial or negative tumor response may potentially be associated with inappropriate drug concentration, non-uniform PEF distribution, and other factors, including immune response to the treatment ( Sersa et al, 2008b ; Cadossi et al, 2014 ).…”
Section: Applications In Vivo and In Clinical Trialsmentioning
confidence: 99%
“…Electrochemotherapy is a combined modality treatment based on electroporation plus concurrent chemotherapy, usually bleomycin, administered intravenously. Electrochemotherapy is mainly used in the palliative setting of skin tumors and metastases7–9 and, more recently, of vulvar cancer 10–12. Recent studies have shown that patients with vulvar cancer relapse and without additional standard treatment options show response rates of approximately 80% after electrochemotherapy 13–15.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of ECT as a treatment has been well demonstrated following the publication of outcome analyses collated from cancer centres across Europe, all demonstrating good response rates [ 1 , 9 , 10 ]. Furthermore, outcome analysis with regards to cutaneous malignancy histiotypes demonstrates the efficacy of ECT across multiple tumour types, including melanoma [ 11 , 12 ], breast cancer [ 13 , 14 ], and basal cell carcinomas (BCCs) [ 15 , 16 ], establishing ECT as a recognised treatment option contributing to the multi-disciplinary management of a variety of cutaneous malignancies.…”
Section: Introductionmentioning
confidence: 99%